Mecanismo mediado por paládio em reação de redução de oxigênio e efeito das vacâncias de oxigênio: Estudo com estruturas ocas de AgPd obtidas por substituição galvânica - PEREIRA, Fellipe dos Santos (2023)
Catalysis plays a key role in converting clean energy into sustainable future technologies. In this study, we designed silica-immobilized AgPd nanoshells for a tunable oxygen reduction reaction mechanism (ORR) based on the metal composition (Ag and Pd) by a galvanic substitution approach. Most importantly, creating oxygen vacancies on the support was essential, a breakthrough result explained by electrochemical impedance spectroscopy (EIS) spectroscopy. Optimizing the proportion of metals meant that the oxygen vacancies' content increased the decrease in the AgPd ratio along the support. Thus, the XPS revealed that Ag+ and Pd2+ species were essential for the increase in vacancies. Interestingly, we observed a decrease in the AgPd ratio compared to a similar Pd-only catalyst, which changed the mechanism from 2 to 4 electrons, showing that Ag38Pd62/SiO2 delivered the best catalytic performance. Furthermore, a computational study of SiO2 oxygen vacancies in AgPd nanoshells was carried out, which supported that the strengths between the nanostructures and the support lead to the establishment of vacancies.